A brief history of the relationship between Futuwwa (Muslim brotherhood) and the Ṣūfī’s tarīqahs in the Islamic civilization - Saparmin, Norzakiah (Research Management Centre, International Islamic University Malaysia, 2016)
Futuwwa or a brotherhood is one of the important social institutions in the Islamic civilization. Although many historians assumed that it has originated from the Persian military organization, it was later known that many of the characteristics of being a part of futuwwa such as generosity, truthfulness, self-sacrificing, hospitality, hardworking had all its roots in the Qurʼān and Sunnah of Prophet Mohammad (SAW) and his beloved Companions. We will delineate briefly a background history of the connection of futuwwa with its Persian roots, and later it was developed and systematized further to be part of the Sūfī institution, and functioned as an influential social institution either in the education and training of acquiring various skills and craftsmanship and contributing towards a thriving local economy, or as an outgoing and influential Sūfī institution in defending and propagating Islam.